2008
DOI: 10.1029/2007gb003107
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate isotopic composition between Bermuda and Puerto Rico: Implications for N2 fixation in the Atlantic Ocean

Abstract: . One important caveat is that fixed N in atmospheric deposition may contribute a significant proportion of the low-d 15 N N in the Sargasso Sea thermocline, in which case the relatively low rate we estimate for N 2 fixation would still be too high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
194
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(215 citation statements)
references
References 73 publications
(172 reference statements)
20
194
1
Order By: Relevance
“…3a). Atmospheric deposition, which is not accounted for in the model, may play an important role in determining the shallow nitrate δ 15 NO 3 in the Atlantic (Knapp et al, 2008). Deep ocean values in the Atlantic are slightly lower than observed, but the observations lie within the envelope of model uncertainty.…”
Section: Model-data Comparisonmentioning
confidence: 82%
“…3a). Atmospheric deposition, which is not accounted for in the model, may play an important role in determining the shallow nitrate δ 15 NO 3 in the Atlantic (Knapp et al, 2008). Deep ocean values in the Atlantic are slightly lower than observed, but the observations lie within the envelope of model uncertainty.…”
Section: Model-data Comparisonmentioning
confidence: 82%
“…Low δ 15 N signatures of particles from sediment traps in the tropical North Pacific (Karl et al, 1997Scharek et al, 1999a, b) and Atlantic (Altabet, 1988;Bourbonnais et al, 2009;Knapp et al, 2005;Mahaffey et al, 2003) suggest that at least part of the recently fixed N is ultimately exported out of the photic zone. Knapp et al (2008) and Bourbonnais et al (2009) also observed a low δ 15 N of NO − 3 (relative to δ 18 O-NO − 3 ) in surface waters in the western and eastern subtropical Atlantic Ocean, supporting the role of N 2 fixers in these regions. Böttjer et al (2017) revealed that N 2 fixation supports 26-47 % of particulate N (PN) export over a 9-year time series (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) period at station ALOHA (North Pacific Subtropical Gyre).…”
Section: Introductionmentioning
confidence: 88%
“…It does not include any new production due to nitrogen fixation, zooplankton migration, or atmospheric deposition of nitrate. At BATS, nitrogen fixation has been estimated to be 0.03 to 0.08 mol N m −2 yr −1 (Singh et al, 2013;Knapp et al, 2008), which is equivalent to 5 to 12 % of the new production we report from the flux gauge method. Zooplankton migration from 2003 to 2006 has been estimated to support a new production of 2 g C m −2 yr −1 (Steinberg et al, 2012), which is equivalent to 0.025 mol N m −2 yr −1 using the revised Redfield ratios of Anderson and Sarmiento (1994) and thus is only 4 % of the new production rate estimated by the flux gauge technique.…”
Section: The Fluxes Of Helium-3 and Nitratementioning
confidence: 99%
“…Net community production has been estimated from the seasonal accumulation of O 2 / Ar (Spitzer and Jenkins, 1989) and the drawdown of dissolved inorganic carbon (Gruber et al, 1998;Brix et al, 2006;Fernandez-Castro et al, 2012). New production has been estimated from bottle incubations (Lipschultz, 2001;Lipschultz et al, 2002) and has also been studied using nitrogen isotopes (Fawcett et al, 2014;Knapp et al, 2008).…”
Section: Data Collectionmentioning
confidence: 99%